An improved wavelet de-noising-based back propagation neural network model to forecast the bioaerosol concentration. Issue 3 (12th November 2020) - Li, Xiaonan; Cheng, Xi; Wu, Wenjian; Wang, Qinghua; Tong, Zhaoyang; Zhang, Xiaoqing; Deng, Dahai; Li, Yihe; Gao, Xinbao
Abstract: Detection, monitoring and estimation of bioaerosol concentration have become increasingly important for several reasons, particularly for environmental quality monitoring and public health concerns on these materials. Bioaerosol concentration is highly variable and noisy, influenced by many factors including meteorological parameters. Directly predicting bioaerosol concentration with noisy data gives erroneous results. As such, we developed a facile approach to forecast bioaerosol concentration using the Wavelet De-noising-based Back Propagation (WDBP) neural network model. We used meteorological data for Changsha gathered from 1 November 2018 to 1 April 2019 to demonstrate the efficiency of WDBP neural network in forecasting atmospheric bioaerosol concentration. The superiority of the new approach over the single Back Propagation (BP) neural network was also validated using real dataset. Overall, the performance of WDBP neural network was satisfactory, underlying potential practical application of the method in forecasting bioaerosol concentration. This work provides a prospective model, useful in monitoring environmental quality and atmospheric bio-threats to public health. Copyright © 2020 American Association for Aerosol Research